2019
DOI: 10.3389/fphys.2019.01249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training and IL-6 Receptor Blockade on Gastric Emptying and GLP-1 Secretion in Obese Humans: Secondary Analyses From a Double Blind Randomized Clinical Trial

Abstract: BackgroundInterleukin-6 (IL-6) is released from skeletal muscle during exercise and systemic IL-6 levels therefore increase acutely in response to a single bout of exercise. We recently showed that an acute increase in IL-6 delayed gastric emptying rate and improved postprandial glycemia. Here we investigate whether repeated increases in IL-6, induced by exercise training, influence gastric emptying rate and moreover if IL-6 is required for exercise-induced adaptations in glycemic control including secretion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Interestingly, in humans, the exercise‐induced reduction in fat mass was recently shown to be dependent on intact IL‐6 signaling. Indeed, IL‐6 receptor blockade with tocilizumab prevented the reduction in visceral AT mass caused by exercise training (52), supporting prior literature that muscle‐derived IL‐6 is an important signaling mediator during exercise that may contribute to long‐term exercise adaptations (summarized in Pedersen and Febbraio) (53).…”
Section: Exercise and At Remodeling In Obesitysupporting
confidence: 73%
“…Interestingly, in humans, the exercise‐induced reduction in fat mass was recently shown to be dependent on intact IL‐6 signaling. Indeed, IL‐6 receptor blockade with tocilizumab prevented the reduction in visceral AT mass caused by exercise training (52), supporting prior literature that muscle‐derived IL‐6 is an important signaling mediator during exercise that may contribute to long‐term exercise adaptations (summarized in Pedersen and Febbraio) (53).…”
Section: Exercise and At Remodeling In Obesitysupporting
confidence: 73%
“…Three intervention studies in similar cohorts also found no effect of less strenuous but more time‐consuming interval training (3–6 sessions per week: 6–10 × 2–3 min intervals at ∼80% VO 2 max or ∼90% HRmax, total time consumption 45–60 min) on overall GLP‐1 (Heiston et al, 2019; Lehrskov et al, 2019; Malin et al, 2018) and GIP (Malin et al, 2018) responses to OGTTs or mixed meal tests. This is in line with results from most moderate‐intensity, continuous endurance training intervention studies.…”
Section: Discussionmentioning
confidence: 98%
“…Adaptively decreased fasting (Kullman et al, 2016; Martins, Kulseng, Rehfeld, King, & Blundell, 2013) and oral glucose‐stimulated (Kullman et al, 2016) incretin hormone concentrations have also been reported following moderate‐intensity, continuous endurance training interventions. However, results are conflicting, and most studies find no effect of high‐volume, moderate‐intensity, continuous endurance (Chanoine et al, 2008; Ellingsgaard et al, 2020; Gibbons et al, 2017; Malin et al, 2018; Malkova et al, 2020; Martins, Kulseng, King, Holst, & Blundell, 2010; Ueda et al, 2013; Weiss et al, 2015) or interval training (Heiston et al, 2019; Lehrskov et al, 2019; Malin et al, 2018; Shakiba, Sheikholeslami‐Vatani, Rostamzadeh, & Karim, 2019) on fasting and postprandial incretin hormone levels. The effect of more strenuous but time‐efficient, very low‐volume HIT on incretin hormone concentrations has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, IL-6 activities are often enhanced by exercise or as a consequence of an active lifestyle [162][163][164] . Systemic changes in IL-6 following physical exercise affects glucose disposal and insulin sensitivity [165][166][167] .…”
Section: Metabolism-mentioning
confidence: 99%